LANTAI HIDROLIS PADA RUMAH PANGGUNG STUDI KASUS: RUMAH PANGGUNG DI KELURAHAN KEMIJEN SEMARANG - IM. Tri Hesti Mulyani; Etty E. Listiati; B. Tyas Susanti; Widija Suseno (PROSIDING SNAST, 2018)
Rising sea levels and land subsidence in Semarang caused several areas in Semarang suffering of tidal floods (sea water intrusion). This problem can be found mainly in the areas close to the sea.The rate of subsidence in the Tanjung Emas port area is 13.5 cm / year. This has an impact on the residential areas nearby where the areas often hit by tidal floods.One of the settlements that is often hit by tidal floods is Kemijen village, situated in the North Semarang sub-district, Semarang City. Landfilled is te practical solution that is carried out by the residents to elevate the floor of the house so the house can be free from tidal flooding. However, this is temporary solution because every 5 years the floor must be elevated again.One solution for the house structure system adapt tidal flooding is the stage house system. However, along with the rate of land subsidence and rising tidal flood water level, the floor level of the house's stage will become closer to the tidal flood water surface. In order to overcome the rising water level, the alternative construction that can be done is by applying "hydraulic floor construction". The hydraulic floor means the floor of the house which can be raised manually by using jack tool. To facilitate the process of raising the floor (hydraulic process), a 3x3 meter floor size module is determined so that the hydraulic process can be carried out optimally.